2020
DOI: 10.1186/s13058-020-01329-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI background parenchymal enhancement, fibroglandular tissue, and mammographic breast density in patients with invasive lobular breast cancer on adjuvant endocrine hormonal treatment: associations with survival

Abstract: Background: To investigate if baseline and/or changes in contralateral background parenchymal enhancement (BPE) and fibroglandular tissue (FGT) measured on magnetic resonance imaging (MRI) and mammographic breast density (MD) can be used as imaging biomarkers for overall and recurrence-free survival in patients with invasive lobular carcinomas (ILCs) undergoing adjuvant endocrine treatment. Methods: Women who fulfilled the following inclusion criteria were included in this retrospective HIPAA-compliant IRB-app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In addition, Choi et al showed moderate or marked BPE on pre-NAC MRI was independently associated with worse recurrence-free survival [84], while Lim et al showed an association between non-minimal BPE and worse recurrence-free survival in postmenopausal women [66]. In contrast, two recent studies have shown no correlation with recurrence [85,86]. Another study evaluated BPE qualitatively and quantitatively before and after NAC and found that only post-therapeutic quantitative BPE predicted recurrence [77].…”
Section: Prognosismentioning
confidence: 99%
“…In addition, Choi et al showed moderate or marked BPE on pre-NAC MRI was independently associated with worse recurrence-free survival [84], while Lim et al showed an association between non-minimal BPE and worse recurrence-free survival in postmenopausal women [66]. In contrast, two recent studies have shown no correlation with recurrence [85,86]. Another study evaluated BPE qualitatively and quantitatively before and after NAC and found that only post-therapeutic quantitative BPE predicted recurrence [77].…”
Section: Prognosismentioning
confidence: 99%